Effect of Seed Orientation, Media and Container Types on Germination Behaviour and Seedling Growth of Swietenia macrophylla King under Nursery Conditions - S. ABDUL KADER,; K.K. SEETHALAKSHMI, (Seed Research, 2026)
A study was undertaken in the nursery at Kerala Forest Research Institute, Peechi (10° 31' N latitude and 76° 20° E longitude; Mean annual rainfall 2700 mm; Mean annual temperature 18° C to 38.4° C) to test the effect of seed orientation, media and container types on germination and seedling growth of Swietenia macrophylla King. Seeds were sown in three different positions. Orientation of seeds during sowing had significant effect on germination of seeds as well as seedling growth. Sowing the seeds horizontally with the micropyle oriented laterally gave the maximum germination of 92 per cent as against 87 per cent by vertical sowing. But seeds sown inverted with the micropyle positioned upwardly gave only 11 per cent germination. Similarly, plant percentages were also higher in horizontal sowing (92%) than in vertical (82%) and inverted sowings (11%). Seeds were also sown in three different germination media such as river sand, garden soil and vermiculite. Although, there is no statistical difference between media on seed germination and subsequent seedling growth, obviously there is a difference between them. River sand medium was superior (98%), followed by garden soil (95%) and vermiculite (93%). Both the seed orientation and germination media significantly affected the rate of germination also. Earliest germination was observed in horizontal position sowing (13 DAS) followed by vertical (14 DAS) and inverted positions (19 DAS). Similarly, earliest germination was observed equally in river sand and garden soil (12 DAS) and culminated on 22 DAS. In vermiculite, seedling emergence was little delayed (15 DAS) and prolonged for sometime (29 DAS). Also incidence of abnormal seedlings was high in vermiculite medium (5.3%) than in garden soil (2.6%) and river sand (1.3%) media. Different containers did affect the growth of seedlings in the nursery. Polypotted seedlings are ready for field planting after 3 months while root trainer seedlings after 5-6 months. However, the polypotted seedlings can be kept for up to 5 months in the nursery since root coiling occurs afterwards where as root trainer seedlings can be kept for more than one year in the nursery.